The impact of somatic SMAD4 mutations in colorectal liver metastases - Xourafas, Dimitrios; Mizuno, Takashi; Cloyd, Jordan M. (Chinese Clinical Oncology; Vol 8, No 5 (October 09, 2019): Chinese Clinical Oncology (Molecular Markers in Colorectal Cancer), 2019)
Recent advances in cancer genomics have led to the identification of many molecular pathways involved in colorectal cancer (CRC) carcinogenesis. Pre-clinical and clinical data have shown that gene mutations involved in several of these pathways have an important prognostic impact, particularly on the outcomes of patients with metastatic CRC. Therefore, specific information on such gene mutational status can be potentially used as biomarkers to guide genome-oriented personalized treatment and ultimately improve patient outcomes. Drosophila protein, mothers against decapentaplegic homolog 4 (SMAD4) has a critical intermediate role in the TGFβ signaling pathway. Loss of SMAD4 expression is associated with both metastatic development and worse response to chemotherapy for patients with CRC. Additionally, it has been reported that the loss of SMAD4 function is independently associated with decreased recurrencefree (RFS) and overall survival (OS) for patients with CRC, especially for patients with advanced stages of disease. Furthermore, among patients who undergo hepatectomy for colorectal liver metastases (CRLM), SMAD4 mutations are associated with a high likelihood of simultaneously carrying RAS mutations, which independently predict worse OS. Although recent evidence highlights the prognostic importance of somatic SMAD4 mutations in CRLM, ongoing research is necessary to untangle the specific molecular mechanisms involved in the complex SMAD4 regulatory network as well as the synergism with other mutations implicated in the pathogenesis of CRC. The detailed elucidation of such mechanisms may potentially aid the development of future trials in establishing novel, targeted therapeutic advances to further guide clinical decision-making for patients with CRC.